2006
DOI: 10.1017/s1360674306001808
|View full text |Cite
|
Sign up to set email alerts
|

The history of the genitive case from the Old English period onwards

Abstract: The history of the genitive case from Old English onwards, specifically the diversity of genitival functions in Old English, and the subsequent development of the case as determiner marker as claimed in Rosenbach (2002), can be explained coherently by assuming NP status for genitive nominals and nondistinct categorial status of the determiner class in OE. This article argues that OE, as an inflected language, encodes events in terms of roles carried by participants, and that the genitive case signalled partial… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2008
2008
2015
2015

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(10 citation statements)
references
References 20 publications
0
10
0
Order By: Relevance
“…Evidence for this increase in frequency, as discussed by Koike (2004Koike ( , 2006, comes from the data provided by Thomas (1931: 70). He suggests that the frequency of the prenominal [X Y] (52%) is almost the same as the postnominal genitive [Y X] (47.5%) in early OE prose; early OE poetry already favours prenominal possessives (77.3%) rather than postnominal ones (22.4%), with the remainder being instances of the ofperiphrasis; but prenominal possessives in prose continue to grow to about the twelfth century, when the rise of the of-periphrasis results in decrease of prenominal possessives in both poetry and prose (cf.…”
Section: Variability In Old Englishmentioning
confidence: 86%
See 1 more Smart Citation
“…Evidence for this increase in frequency, as discussed by Koike (2004Koike ( , 2006, comes from the data provided by Thomas (1931: 70). He suggests that the frequency of the prenominal [X Y] (52%) is almost the same as the postnominal genitive [Y X] (47.5%) in early OE prose; early OE poetry already favours prenominal possessives (77.3%) rather than postnominal ones (22.4%), with the remainder being instances of the ofperiphrasis; but prenominal possessives in prose continue to grow to about the twelfth century, when the rise of the of-periphrasis results in decrease of prenominal possessives in both poetry and prose (cf.…”
Section: Variability In Old Englishmentioning
confidence: 86%
“…English possessive constructions have been analysed in a monograph length study by Rosenbach (2002), and within a Cognitive Grammar framework in some detail, both synchronically (for example, by Taylor 1996) and diachronically (for example, by Koike 2004Koike , 2006. In this section, I discuss some of the ways in which possessive constructions have developed in the history of English.…”
Section: Some Data On the Development Of Possessive Constructionsmentioning
confidence: 99%
“…The premodifier genitive signifies the closest relation and minimal individuation; the determiner genitive signifies the most distant relation and maximal individuation. Compare Koike (2006) on limited involvement as the meaning of the genitive in English.…”
Section: The Nature Of the Genitive And Of Casementioning
confidence: 99%
“…If we follow Rosenbach (2002), Stefanowitsch (2003), Koike (2006), Hinrichs and Szmrecsanyi (2007) among others in regarding both forms as genitive, then the nominal premodifiers being considered must also be deemed to be genitives. What links the -s and of-forms in that view is their shared set of underlying relations, and that is shared equally by these nominal premodifiers.…”
Section: Introductionmentioning
confidence: 99%
“…Investigations into prenominal and postnominal genitives have shown that it is the latter-a category that essentially includes the partitive genitive illustrated in (15) and (16) below (Allen 1998;Koike 2006 (2) This change reflects the loss of postnominal genitives, while some prenominal ones continued into late ME, accompanied by a steep increase in the frequency of the of genitive (Thomas 1931). The partitive genitive is the last postnominal type to disappear from English, although its use does not extend beyond the thirteenth century (Allen 1998).…”
mentioning
confidence: 99%